Women, Crime and Language - Gray, F. author. aut Link
VIII, 216 p.
Keywords: Women, Crime and Language examines the relationships between discourses of crime and gender: how women are represented in fiction and reportage, and how they have represented themselves. Frances Gray explores a number of high-profile cases from the Whitechapel Murders of 1888 to the Children's Home scandals of the present day, in which women have featured as victims, perpetrators or investigators. The author tracks the representation of women through detective stories, plays and novels.